1992
DOI: 10.1042/bj2830021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by casein kinase II alters the biological activity of calmodulin

Abstract: Calmodulin is the major intracellular Ca(2+)-binding protein, providing Ca(2+)-dependent regulation of numerous intracellular enzymes. The phosphorylation of calmodulin may provide an additional mechanism for modulating its function as a signal transducer. Phosphocalmodulin has been identified in tissues and cells, and calmodulin is phosphorylated both in vitro and in intact cells by various enzymes. Phosphorylation of calmodulin on serine/threonine residues by casein kinase II decreases its ability to activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…This result is in agreement with our prior results that used other CaM-dependent enzymes to demonstrate that phosphorylation of CaM does not change the protein's affinity for calcium (24).…”
Section: Ck2 Treatment Of Cam Ser-81 Phosphorylation-site Mutants In supporting
confidence: 83%
“…This result is in agreement with our prior results that used other CaM-dependent enzymes to demonstrate that phosphorylation of CaM does not change the protein's affinity for calcium (24).…”
Section: Ck2 Treatment Of Cam Ser-81 Phosphorylation-site Mutants In supporting
confidence: 83%
“…In support of this, it has been shown that phosphorylation of calmodulin by casein kinase-2 (an insulin-sensitive and EGF-sensitive serinehhreonine kinase) alters the biological activity of calmodulin by decreasing the activation of two calmodulin-dependent enzymes, myosinlight chain kinase and cyclic-nucleotide phosphodiesterase (Sacks et al, 1992a). Additionaly, phosphorylation of calmodulin in Tyr99 by the insulin receptor decreases the action of calmodulin antagonists on the type-I cyclic-nucleotide phosphodiesterase, although it does not affect the calmodulin dependency of this enzyme (Saville and Houslay, 1994).…”
mentioning
confidence: 99%
“…Recently we have demonstrated that the epidermal growth factor (EGF) receptor can be isolated by calmodulin-affinity chromatography, and that calmodulin inhibits its tyrosine lunase activity (San JosC et al, 1992). Calmodulin, therefore, could potentially play a regulatory role in the EGF-mediated mitogenic-signal pathway.Calmodulin has been shown to be a substrate for several different protein kinases (Plancke and Lazarides, 1983 ;Hiiring et al, 1985;Fukami et al, 1985;Graves et al, 1986;Lin et al, 1986;Nakajo et al, 1986Nakajo et al, , 1988Meggio et al, 1987Meggio et al, , 1992Kubo and Strott, 1988;Sacks and McDonald, 1988;Laurino et al, 1988; Sacks et al, 1989aSacks et al, , 1992aSan JosC et al, 1992;Benguria et al, 1993;Saville and Houslay, 1994). Since this phosphorylation process occurs in intact …”
mentioning
confidence: 99%
“…Moreover, calmodulin phosphorylation is regulated in vivo by insulin (Colca et al, 1987;Sacks et al, 1992a;Joyal and Sacks, 1994), which sigiiificantly enhances phosphate incorporation at serine, threonine and tyrosine residues (Sacks et al, 1992a). The interaction between calmodulin and several calmodulin-dependent enzymes has been studied in detail in vitro using purified components (Cohen and Klee, 1988).…”
mentioning
confidence: 99%
“…Phosphorylation is a cotnmon mechanism for the regulation of intracellular signalling and calmodulin is known to be phosphorylated in vitro by several protein kinases. The best characterized of these are casein kinase 11 (Nakajo et al, 1986;Sacks et al, 1992a) and the insulin-receptor kinase (Graves et al, 1986;Sacks and McDonald, 1988;Sacks et al, 1989). The sites phosphorylated on callmodulin are Thr79 (14%), Ser8l(SO%), Serl01(25%) and Thrl17 (1 1 %) by casein kinase 11 (values in parentheses are the relative amounts of phosphorylation at each site, expressed as percentage of total '2P incorporation; Sacks et al, 1992a) and both tyrosine residues, namely Tyr99 and Tyr138, by the insulin-receptor kinase (Joyal and Sacks, 1994;Williams et al, 1994).…”
mentioning
confidence: 99%